2014
DOI: 10.1128/ec.00248-13
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression and Focused Knockout Analysis Reveals Genes Associated with Fungal Fruiting Body Development in Neurospora crassa

Abstract: Fungi can serve as highly tractable models for understanding genetic basis of sexual development in multicellular organisms. Applying a reverse-genetic approach to advance such a model, we used random and multitargeted primers to assay gene expression across perithecial development in Neurospora crassa. We found that functionally unclassified proteins accounted for most upregulated genes, whereas downregulated genes were enriched for diverse functions. Moreover, genes associated with developmental traits exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 83 publications
(100 reference statements)
3
113
0
Order By: Relevance
“…For example, RMAexpress (http://rmaexpress.bmbolstad.com) analysis of normalized raw data obtained from microarray analysis using P. chrysogenum strain P2niaD18 revealed relative MAT1‐1‐1 expression levels of about 13.6% and 3.1% referred to actin ( Pc20g11630 ) and myosin ( Pc21g00710 ) expression levels, respectively (http://onlinelibrary.wiley.com/doi/10.1111/mmi.12987/suppinfo) (Böhm et al ., ). Furthermore, transcripts of mating‐type genes were reported to be barely detectable by Northern hybridization in Podospora anserina as well as RNA‐seq analysis in Neurospora crassa (Coppin and Debuchy, ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…For example, RMAexpress (http://rmaexpress.bmbolstad.com) analysis of normalized raw data obtained from microarray analysis using P. chrysogenum strain P2niaD18 revealed relative MAT1‐1‐1 expression levels of about 13.6% and 3.1% referred to actin ( Pc20g11630 ) and myosin ( Pc21g00710 ) expression levels, respectively (http://onlinelibrary.wiley.com/doi/10.1111/mmi.12987/suppinfo) (Böhm et al ., ). Furthermore, transcripts of mating‐type genes were reported to be barely detectable by Northern hybridization in Podospora anserina as well as RNA‐seq analysis in Neurospora crassa (Coppin and Debuchy, ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…6A). Similar to PUK1, the transcription level of NCU03242 was relatively low, and A-to-I editing events were not observed in vegetative hyphae and other developmental stages in N. crassa (Wang et al 2014). Interestingly, the PUK1 ortholog in F. verticillioides (FVEG_ 01191) has a stop codon that is equivalent to the second of two tandem stop codons in its ORF.…”
Section: None Of the Adat Genes In F Graminearum Is Specifically Expmentioning
confidence: 92%
“…6A). Comparative analysis of published RNA-seq data (Wang et al 2014) revealed that the A-to-I editing event at this site (UAGUGG to UGGUGG) also occurs in the transcripts of NCU03242 in perithecia (Fig. 6A).…”
Section: None Of the Adat Genes In F Graminearum Is Specifically Expmentioning
confidence: 99%
“…Fruiting body mutants are now available for many fungi other than P. anserina, including Sordaria macrospora [27], N. crassa [28], A. nidulans [29] and Coprinopsis cinerea (formely Coprinus cinereus) [30,31] and could be analyzed using similar methods. They are complementary to the now more widespread large scale analyses of transcriptomes during fruiting body development as performed in the ascomycetes Fusarium graminearum and Fusarium verticilloides [32][33][34], N. crassa [35,36], S. macrospora [37], Pyronema confluens [38], Tuber melanosporum [39][40][41], Cordyceps militaris [42] and Ophiocordyceps sinensis [43], as well as in the basidiomycetes C. cinerea [44], Moniliophthora perniciosa [45], Agrocybe aegerita [46], Lentinula edodes [47,48], Auricularia polytricha [49] and Ganoderma lucidum [50].…”
Section: Resultsmentioning
confidence: 99%